Quantitative analysis of annealing-induced instabilities of photo-leakage current and negative-bias-illumination-stress in a-InGaZnO thin-film transistors - Wang, Dapeng; Furuta, Mamoru (Beilstein Journal of Nanotechnology, 2019)
This study examines the effect of the annealing temperature on the initial electrical characteristics and photo-induced instabilities of amorphous indium gallium zinc oxide (a-IGZO) thin-film transistors (TFTs). The extracted electrical parameters from transfer curves suggest that a low-temperature treatment maintains a high density of defects in the IGZO bulk, whereas high-temperature annealing causes a quality degradation of the adjacent interfaces. Light of short wavelengths below 460 nm induces defect generation in the forward measurement and the leakage current increases in the reverse measurement, especially for the low-temperature-annealed device. The hysteresis after negative-bias-illumination-stress (NBIS) is quantitatively investigated by using the double-scan mode and a positive gate pulse. Despite the abnormal transfer properties in the low-temperature-treated device, the excited holes are identically trapped at the front interface irrespective of treatment temperature. NBIS-induced critical instability occurs in the high-temperature-annealed TFT.
Keywords: metal oxide; photo-induced instabilities; photon energy; thermal annealing; thin-film transistor (TFT) device

(untitled) - Nomura, K.; Ohta, H.; Takagi, A.; Kamiya, T.; Hirano, M.; Hosono, H. (Nature, 2004)

(untitled) - Chowdhury, M. D. H.; Um, J. G.; Jang, J. (Appl. Phys. Lett., 2014)

(untitled) - Shimakawa, S.-i.; Kamada, Y.; Kawaharamura, T.; Wang, D.; Li, C.; Fujita, S.; Hirao, T.; Furuta, M. (Jpn. J. Appl. Phys., 2012)

(untitled) - Kimura, M.; Furuta, M.; Kamada, Y.; Hiramatsu, T.; Matsuda, T.; Furuta, H.; Li, C.; Fujita, S.; Hirao, T. (IEEE Trans. Electron Devices, 2011)

(untitled) - Eom, T.-Y.; Ahn, C.-H.; Kang, J.-G.; Salman, M. S.; Lee, S.-Y.; Kim, Y.-H.; Lee, H.-J.; Kang, C.-M.; Kang, C. (Appl. Phys. Express, 2018)

(untitled) - Kim, J.; Bang, J.; Nakamura, N.; Hosono, H. (APL Mater., 2019)

(untitled) - Lee, M.; Kim, M.; Jo, J.-W.; Park, S. K.; Kim, Y.-H. (Appl. Phys. Lett., 2018)

(untitled) - Wang, D.; Furuta, M. (Beilstein J. Nanotechnol., 2018)

(untitled) - Kim, Y. J.; Yang, B. S.; Oh, S.; Han, S. J.; Lee, H. W.; Heo, J.; Jeong, J. K.; Kim, H. J. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Wang, Y.; Sun, X. W.; Goh, G. K. L.; Demir, H. V.; Yu, H. Y. (IEEE Trans. Electron Devices, 2011)

(untitled) - Wang, D.; Zhao, W.; Furuta, M. (J. Phys. D: Appl. Phys., 2019)

(untitled) - Furuta, M.; Kamada, Y.; Kimura, M.; Hiramatsu, T.; Matsuda, T.; Furuta, H.; Li, C.; Fujita, S.; Hirao, T. (IEEE Electron Device Lett., 2010)

(untitled) - Hung, M. P.; Wang, D.; Jiang, J.; Furuta, M. (ECS Solid State Lett., 2014)

(untitled) - Chang, G.-W.; Chang, T.-C.; Jhu, J.-C.; Tsai, T.-M.; Syu, Y.-E.; Chang, K.-C.; Tai, Y.-H.; Jian, F.-Y.; Hung, Y.-C. (Appl. Phys. Lett., 2012)

(untitled) - Kim, S. J.; Kim, H. T.; Choi, J. H.; Chung, H. K.; Cho, S. M. (Appl. Phys. Lett., 2018)